The Cumulation of Debris Clouds around a Fast-rotating Asteroid - Chenyang Huang; Yang Yu; Zhijun Song; Bin Cheng; Patrick Michel; Hexi Baoyin (The Astrophysical Journal)
The rotational mass loss has been realized to be a prevalent mechanism to produce low-speed debris near the asteroid, and the size composition of the asteroid’s surface regolith has been closely measured by in situ explorations. However, the full-scale evolution of the shedding debris has not been examined using the observed particle sizes, which may hold vital clues to the initial growth of an asteroid moonlet and help us to understand the general mechanisms that dominate the formation of asteroid systems. This paper presents our study on the cumulative evolution of the debris cloud formed by a rotationally unstable asteroid. A semianalytical model is developed to characterize the spatiotemporal evolution of the debris cloud posterior to a shedding event. Large-scale discrete element method (DEM) simulations are performed to quantify the clustering behavior of the debris particles in the mechanical environment near the asteroid. As a result, we found that the cumulation of a steady debris cloud is dominated by large pieces of debris, and the shedding particles follow a common migration trend, which fundamentally determines the mass distribution of the debris cloud. For the accretion analysis, we sketched the life cycle of a debris cluster and showed its dependency on particle size. The DEM simulations adopt physical parameters estimated from observations and asteroid missions. The results confirm that porous fluffy cluster structures can form shortly after a shedding event with magnitudes the same as the observed shedding activities. Measurements of these structures show that they themselves possess a certain strength and have the capacity to collisions to absorb dissociative particles that collide with them.